Principles of marketing - Kotler, Philip T.; Armstrong, Gary (New York, NY Pearson, 2018)
Book packed with stories illustrating how companies use new digital technologies to maximize customer engagement and shape brand conversations, experiences, and communities.
Keywords: Quản trị kinh doanh